Assessment of the radioactivity of phosphogypsum at the General Phosphate Company in Anbar Governorate, Iraq - Al-Gharrawy, Mazen; Al-Rubaye‎, Ibtihal; Alqaisi , ‎Zaki ‎ (ASJ - Academic Science Journal, 2026)
This study evaluates the potential radiological hazards associated with phosphogypsum waste; a byproduct generated by the General Company for Phosphates. Phosphogypsum waste is often considered an environmental hazard because it contains naturally occurring radioactive materials, primarily 226Ra. To assess the radioactivity levels in the phosphogypsum waste, 10 samples were collected from different locations. The samples were analyzed using high-purity germanium gamma spectrometry. The average activity concentration of 226Ra was 640.8 ± 12.3 Bq/kg. This level falls well within the international standard range established for 226Ra (15–1140 Bq/kg) and indicates that the radiological characteristics of the locally sourced material are comparable to those reported for other industrial sites worldwide. This study provides important baseline data on the radioactivity present in locally produced phosphogypsum waste, which may inform future environmental quality assessments and the development of safe waste management strategies.